Um desafio cotidiano: aprender a conviver com as vozes - Bender, Andrea Regina Molina Jaekel; Tavares, Diogo Henrique; Coradini, Djeniffer Rodrigues; Lopes, Ivon Fernandes; Farias, Izamir Duarte; da Silva, Larissa Dall’ Agnol; Ubessi, Liamara Denise; Silveira, Priscila Borges (Journal of Nursing and Health, 2018)
-